Wojciech Zamecznik 1923-1967. (Warszawa : National Museum in Warsaw, 1968)
From Wikipedia, the free encyclopedia: Wojciech Zamecznik (13 January 1923 – 12 May 1967, Warsaw) was a Polish graphic artist, architect, photographer and interior designer. Brother of Stanislaw Zamecznik, graphic artist, poster artist, scenographer and architect.Zamecznik's most notable works are movie and socio-political posters. He created his own, ascetic poster style which was derived from traditional forms of constructivism and Bauhaus. He was also an author of book graphics and magazine designs.
Adlib record nr. 530007732
Pools
Engels
Wojciech Zamecznik 1923-1967.
boek
Keywords: Zameczik, Wojciech; 1940 - 1967; eigen tijd; Polen